Effect of aging treatment on the microstructure and flow behavior of 6063 aluminum alloy compressed over a wide range of strain rate. (April 2016) - Ye, Tuo; Li, Luoxing; Guo, Pengcheng; Xiao, Gang; Chen, Ziming
Highlights: The cast 6063 alloy under solution treated (ST) and artificial aged (AA) were impacted at strain rates in the range of 1 × 10 −3 to 3.5 × 10 3  s −1 . The AA alloy exhibits an obvious positive strain rate sensitivity under dynamic compression. For the ST alloy, slight strain rate sensitivity is detected. The microstructure evolution during impact deformation resulted in different flow behaviors has been discussed in detail. The modified constitutive equation seems to be consistent with the experimental results. Abstract: The compression deformation behavior of an as-casting 6063 aluminum alloy has been studied under quasi-static and impact loading conditions at strain rate ranges from 1 × 10 −3 to 3.5 × 10 3  s −1 and a constant strain of 0.2. The results showed that the flow stress response of the as-casting 6063 alloy was sensitive to the aging treatment as well as strain rate. For the solution treated (ST) alloy, slight strain rate sensitivity was detected both under quasi-static and dynamic loading. However, the artificial aging (AA) alloy exhibits an obvious positive strain rate sensitivity under dynamic compression, while the sensitivity under quasi-static compression is low. The constants of the modified Johnson–Cook constitutive model were determined by using the measured flow stress data, which was consistent with the experimental results. Dislocations in the form of vein or cell structures with thick walls containing many parallel dislocation lines were observed in the ST alloy under high strain rate loading. By contrast, a relative high density of dislocations and a large number of homogeneous distributed needle-like β ′′ precipitates were detected in the matrix of deformed AA samples. As compared with the AA alloy, the strain hardening and strain rate hardening of ST alloy are balanced by the thermal softening, which results from the adiabatic temperature rise during dynamic deformation. The interactions among them are related to the initial and corresponding evolved microstructure, which leads to its insensitivity to the applied strain rate.